The Role of Glial Cells and Synapse Loss in Mouse Models of Alzheimer’s Disease - Ziegler-Waldkirch, Stephanie; Meyer-Luehmann, Melanie (Frontiers in Cellular Neuroscience, 2018)
Synapse loss has detrimental effects on cellular communication, leading to network disruptions within the central nervous system (CNS) such as in Alzheimer’s disease (AD). AD is characterized by a progressive decline of memory function, cognition, neuronal and synapse loss. The two main neuropathological hallmarks are amyloid-β (Aβ) plaques and neurofibrillary tangles. In the brain of AD patients and in mouse models of AD several morphological and functional changes, such as microgliosis and astrogliosis around Aβ plaques, as well as dendritic and synaptic alterations, are associated with these lesions. In this review article, we will summarize the current literature on synapse loss in mouse models of AD and discuss current and prospective treatments for AD.